Fingerprinting sediment sources in a large agricultural catchment under no‐tillage in Southern Brazil (Conceição River). (13th March 2018) - Tiecher, Tales; Minella, Jean Paolo Gomes; Evrard, Olivier; Caner, Laurent; Merten, Gustavo Henrique; Capoane, Viviane; Didoné, Elizeu Jonas; dos Santos, Danilo Rheinheimer
Abstract: Brazil is a leader in the adoption of conservation agriculture practices and technologies. However, the impact of these practices on sediment sources at the catchment scale has not been quantified yet, particularly in grain growing regions, where a conservationist no‐tillage system is implemented to protect soils. To address this knowledge gap, a sediment fingerprinting study based on elemental geochemistry was carried out in a large agricultural catchment (804 km 2 ) of Southern Brazil where no‐tillage practices dominate. A total of 156 soil samples were taken to characterize the three main potential sediment sources: cropland ( n = 79), unpaved roads ( n = 41), and channel banks ( n = 36). Sediment sampling was performed using a time‐integrated sampler ( n = 33) and by collecting fine‐bed material ( n = 34) at five locations across the catchment. Sediment was also sampled during flood events at the catchment outlet ( n = 20). Sediment source contributions were calculated using an optimal suite of geochemical properties and a mixing model. Results showed that although the catchment is not particularly sensitive to soil erosion (i.e., deep clayey soils with gentle slopes), the amount of sediment supplied by cropland to the river network remains very high (up to 1.63 Mg·ha −1 ·year −1 ). Sediment fingerprinting results showed that even when no‐tillage is implemented, cropland remains an important source of sediment, supplying up to 70% of the material transiting the Conceição River. Accordingly, the current conservation farming system in this catchment needs to be improved to further reduce soil erosion and sediment yield.